2022
DOI: 10.3389/fmed.2022.934989
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum ferritin level and the various stages of non-alcoholic fatty liver disease: A systematic review

Abstract: IntroductionNon-alcoholic fatty liver disease (NAFLD) has become the most common liver disorder across the world, and non-invasive evaluation approaches are in need to assess NAFLD disease progression. Serum ferritin has been proposed as one of the biomarkers for NAFLD diagnosis in previous studies. This systematic review aims to identify, report, and synthesize studies that investigated the association of serum ferritin level with the various stages of NAFLD among the adult population.MethodsThree databases –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Of all subjects with MASLD (n = 2669) in our cohort, 24% (n = 636) had HF, which again supports previous estimates of HF prevalence in MASLD [32]. We also observed a higher prevalence of MASLD of 57% in subjects with HF and a further increase in MASLD prevalence along with the severity of HF [29,[33][34][35]. A relationship between intravenous iron therapy and worsening of hepatic fat was also shown in the setting of dialysis [36] and recently a relationship between liver iron and MASLD was proposed by Mendelian randomization analysis [37].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of all subjects with MASLD (n = 2669) in our cohort, 24% (n = 636) had HF, which again supports previous estimates of HF prevalence in MASLD [32]. We also observed a higher prevalence of MASLD of 57% in subjects with HF and a further increase in MASLD prevalence along with the severity of HF [29,[33][34][35]. A relationship between intravenous iron therapy and worsening of hepatic fat was also shown in the setting of dialysis [36] and recently a relationship between liver iron and MASLD was proposed by Mendelian randomization analysis [37].…”
Section: Discussionsupporting
confidence: 90%
“…Later, the definition of dysmetabolic iron overload (DIOS) was refined as HF with normal or mildly increased transferrin saturation, metabolic abnormalities and a specific amount of hepatic iron excess with liver biopsy or MR imaging [12]. Many reports followed describing the underlying pathophysiology, metabolic alterations [22][23][24][25][26][27][28], the impact of DHF on liver damage [29], or the controversial therapeutic effect of venesection [30]. However, so far, different definitions and criteria for MHF have been used, making comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Kowdley et al showed an independent association between ferritin level and increased risk for liver fibrosis in patients with NAFLD [ 48 ]. On the contrary, two large retrospective studies concluded that even though ferritin was associated with liver steatosis, it was a poor predictor of fibrosis stage and disease progression [ 49 ]. This was in keeping with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) is the most prevalent liver disease in the world. It is characterized by excess intracellular fat in the absence of excessive alcohol consumption ( Wang et al, 2022 ; Jung et al, 2019 ). NAFLD is a disease that progresses in stages starting with simple fatty liver (steatosis), nonalcoholic steatohepatitis (NASH), fibrosis, and cirrhosis, which can lead to liver failure or even hepatocellular carcinoma ( Yang et al, 2022 ; Rostoker et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still uncertainty about its association with NAFLD ( Modares Mousavi et al, 2018 ; Du et al, 2017 ) therefore, its role should be investigated in a large-scale study ( Yang et al, 2022 ; Giacomazzi et al, 2022 ). Many previous studies have suggested that hyperferritinemia is not only associated with NAFLD and systemic inflammation, but also correlates with the histologic severity of NAFLD and with the presence of NASH ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%